Filmy Ferns (Hymenophyllaceae) and Associated Spike-Mosses (Selaginellaceae) from the Mid-Cretaceous Kachin Amber, Myanmar - Ya Li; Yong-Dong Wang; Natalya Nosova; Ning Lu; Yuan-Yuan Xu (Biology, 2022)
Filmy ferns (Hymenophyllaceae) are the most diverse lineage of the early-diverging leptosporangiate ferns with ca. 430 species widely distributed around the world but with the highest diversity in the humid tropics. However, their fossil record is scarce because of the low preservation potential of the delicate, membranous laminae. So far, no Hymenophyllaceae fossils have been reported from tropical Asia. Here, we describe some fern remains and their syninclusions (spike-mosses) in four pieces of Kachin amber from the mid-Cretaceous of Hukawng Valley, Northern Myanmar, as Hymenophyllites angustus sp. nov., H. kachinensis sp. nov., H. setosus sp. nov. (Hymenophyllaceae) and Selaginella alata sp. nov. (Selaginellaceae), respectively. These fern remains are assigned to Hymenophyllaceae based on the filmy, one-cell thick, decompound pinnatifid laminae and dichotomous venation. They represent the first fossil record of Hymenophyllaceae in tropical Asia. The growth habits of these ferns and associated spike-mosses and their implication for paleoenvironment are discussed. Our study expands the diversity of the cryptogams in mid-Cretaceous Kachin amber. Together with other contemporaneous findings, the present fossils indicate that Hymenophyllaceae have already accumulated some notable diversity in the Cretaceous.